A Case of Pituitary Insufficiency in a Patient Presenting with Hyponatremia: Might Be Slow-Progressing Lymphocytic Hypophysitis as a Possible Cause of Empty Sella? - Gülşah Elbüken; Ece Baydar; Sonat Pınar Kara (Turkish Journal of Internal Medicine, 2020)
Case: A 75-year-old female patient presented with complaints of nausea, weakness, fatigue and generalized pain all over her body. Her medical history included essential hypertension, type 2 Diabetes Mellitus, coronary artery disease and hypothyroidism. She was hospitalized due to detecting a serum sodium (Na) concentration of 123 mmol/L. Although her diuretic medications were discontinued and fluid replacement with parenteral hypertonic saline infusion was instituted for approximately 6 days, Na level did not return to normal. Secondary hypothyroidism was considered due to laboratory test results showing low fT4 level and markedly suppressed TSH value. Since further laboratory workup showed that TSH, ACTH, PRL, GH and gonadotropins were also low, the diagnosis was confirmed as “panhypopituitarism”. Her obstetric history was not suggestive of Sheehan’s Syndrome and she did not have a history of head injury or cerebrovascular disease. She was started on parenteral 100 mg hydrocortisone and hormonal replacement therapy with oral levothyroxine. The clinical picture of the patient improved dramatically with resolution of hyponatremia. Results and Discussion: Lymphocytic hypophysitis is an autoimmune disorder of the pituitary gland and it mostly affects middle-aged women. The fact that our patient was the age of 75 without having any clinical symptoms, since she had “panhypopituitarism” and a “partially empty sella” appearance in her pituitary MRI scans, “lymphocytic hypophysitis” was considered as the probably cause of pituitary insufficiency even if her age was older than the typical age of patients affected by the condition. Conclusion: It suggests that slow-progressing primary hypophysitis (probably lymphocytic hypophysitis) can lead to pituitary insufficiency at a later age.